DEVELOPING OF E-LEARNING BASED MATHEMATICS LEARNING MODULES TO IMPROVE PROBLEM SOLVING SKILLS OF STUDENTS - Riyanti, Vera; Budhiarti, Yuli; Istika, Iis (Universitas Sembilanbelas November Kolaka, 2024)
The availability of learning modules that are valid, practical, and easy for students to understand is essential for achieving educational objectives. Additionally, limited problem-solving skills in the fundamental concepts of ordinary differential equations pose a significant challenge in the learning process. This research aims to enhance students' problem-solving abilities in the topic of ordinary differential equations through the development of a mathematics learning e-module for students in the Mathematics Education Study Program. The research method employed is the ADDIE development model. Based on the research findings, the developed e-module was validated by subject matter experts, yielding a score of 3.61, categorized as very good, while validation by media experts resulted in a score of 3.42, also categorized as very good. The evaluation from students regarding the e-module received a score of 3.81, which falls into the very good category. Furthermore, based on the assessment of quiz responses within the e-module, the average score was 78.9, indicating an improvement in students' problem-solving abilities prior to using the e-module, which had an average score of 59.8. It can be concluded that the e-module on the concepts of ordinary differential equations is suitable for use in learning and can enhance students' problem-solving skills.